(untitled) (Journal of Enam Medical College, 2019)
Background: Among term infants, hypoxic-ischemic encephalopathy due to acute perinatal asphyxia remains an important cause of neurodevelopmental deficits in childhood. Treatment is currently limited to supportive intensive care, without any specific brain-oriented therapy. Objective: To determine whether the risk of death or moderate/severe neurodevelopmental impairment in term infants with hypoxic-ischemic encephalopathy increases with relatively high skin or rectal temperature between 12 and 72 hours of birth. Materials and Methods: This was a prospective observational study. Asphyxiated newborns who came within 12 hours of birth were enrolled in this study. Both axillary and rectal temperature were recorded 6 hourly for 72 hours and each infant`s temperature for each site were rank ordered. Then mean of all axillary and rectal temperatures of each neonate was calculated. Outcomes were related to temperatures in logistic regression analyses for the elevated/relatively high temperatures and normal/low temperatures group, with adjustment of the level of encephalopathy and gender. Results: The mean axillary temperature was 36.07 ± 6.10C and in 25.71%, 11.92% and 6.32% cases axillary temperatures were >370C, >37.50C and >380C respectively. The mean rectal temperature was 36.8 ± 60C, and in 43.53%, 30.02% and 19.97% cases rectal temperatures were >370C, >37.50C and >380C respectively. Mean ambient temperature was 26.170C. There was significant correlation between axillary and rectal temperatures (r=0.889). For elevated temperature, the odds of death or moderate to severe impairment increased 8.9-fold (CI 0.906–88.18) and the odds of death alone increased 4.6-fold (CI 0.373–56.83). The odds of impairment increased 1.84-fold (CI 0.45– 7.50). Conclusion: Relatively high temperature during usual care after hypoxic-ischemia in term neonates was associated with adverse neurodevelopmental outcomes. J Enam Med Col 2019; 9(3): 160-165